A Mini Review on Yolk-Shell Structured Nanocatalysts - Sun, Xiaohuan; Han, Jie; Guo, Rong (Frontiers in Chemistry, 2020)
Yolk-shell structured nanomaterials, possessing a hollow shell and interior core, are emerging as unique nanomaterials with applications ranging from material science, biology, and chemistry. In particular, the scaffold yolk-shell structure shows great promise as a nanocatalyst. Specifically, the hollow shell offers a confined space, which keeps the active yolk from aggregation and deactivation. The inner void ensures the pathway for mass transfer. Over the last few decades, many strategies have been developed to endow yolk-shell based nanomaterials with superior catalytic performance. This minireview describes synthetic methods for the preparation of various yolk-shell nanomaterials. It discusses strategies to improve the performance of yolk-shell catalysts with examples for engineering the shell, yolk, void, and related synergistic effects. Finally, it considers the challenges and prospects for yolk-shell nanocatalysts.